Responses of US multinational firms to a temporary repatriation tax holiday: A literature review and synthesis. Issue 1 (December 2019) - Dong, Qi Flora; Cao, Yiting; Zhao, Xin; Deshmukh, Ashutosh
Abstract: The effect of tax policy on the repatriation of foreign earnings is a topic of ongoing discussion among policymakers, academics, and the popular press. It has become more salient due to the 2017 Tax Cuts and Jobs Act (TCJA), which permanently removed repatriation tax. This paper synthesizes the academic literature examining US multinational firms' responses to the repatriation tax holiday initiated by the 2004 American Jobs Creation Act (AJCA), which temporarily reduced the tax on the repatriation of foreign earnings. By synthesizing firm responses to the temporary tax reduction, we identify similarities and differences in: (1) theories about why and when repatriation tax affects firms' repatriation decisions; (2) empirical evidence of whether repatriation tax affects firms' repatriation decisions; and (3) empirical evidence of whether repatriation tax affects firms' investment decisions. The analyses provide insights into the effect of the permanent removal of repatriation tax under the TCJA and explore avenues for future research. This synthesis of the AJCA literature informs tax research and practice as well as policymaking.